2012
DOI: 10.1136/annrheumdis-2012-202450
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of mavrilimumab in subjects with rheumatoid arthritis

Abstract: ObjectivesMavrilimumab, a human monoclonal antibody targeting the alpha subunit of the granulocyte-macrophage colony-stimulating factor receptor, was evaluated in a phase 2 randomised, double-blind, placebo-controlled study to investigate efficacy and safety in subjects with rheumatoid arthritis (RA).MethodsSubcutaneous mavrilimumab (10 mg, 30 mg, 50 mg, or 100 mg) or placebo was administered every other week for 12 weeks in subjects on stable background methotrexate therapy. The primary endpoint was the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 39 publications
7
118
0
3
Order By: Relevance
“…We show here that CBP30 also inhibits GM-CSF cytokine secretion. Th17 cells secreting additional cytokines have been described as being particularly pathogenic, with GM-CSF in particular implicated in rheumatoid arthritis (35). The observed discrepancy between inhibitory effects of CBP30 on GM-CSF secretion and CSF2 transcription might be explained by minor differences in the experimental time course.…”
Section: Discussionmentioning
confidence: 99%
“…We show here that CBP30 also inhibits GM-CSF cytokine secretion. Th17 cells secreting additional cytokines have been described as being particularly pathogenic, with GM-CSF in particular implicated in rheumatoid arthritis (35). The observed discrepancy between inhibitory effects of CBP30 on GM-CSF secretion and CSF2 transcription might be explained by minor differences in the experimental time course.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of GM-CSFRα and CSF-1R has now been tested for clinical efficacy in RA. In the phase II trial of mavrilimumab (anti-GM-CSFRα), all doses combined of mavrilimumab (n = 158) were associated with a significantly higher proportion of patients achieving a ≥ 1.2-point reduction in DAS28-CRP than placebo (n = 75) at Week 12 (55.7% vs 34.7%, p = 0.003) 21 . It is tempting to conclude that the efficacy of mavrilimumab may partly validate the targeting of macrophages, although the cellular pharmacology of GM-CSF antagonism may be complex because of the effect of this cytokine not only on macrophages but also on neutrophils, eosinophils, and perhaps other cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, neutralization/blocking Abs are a useful approach and can easily receive clinical applications. Now, Mavrilimumab, anti-GM-CSF receptor a Ab, is being developed, and a phase II study in subjects with rheumatoid arthritis patients is reported to have significant efficacy and no serious adverse events, including PAP (54). Regarding the fact that neutralization of GM-CSF ameliorated ILD in SKG mice even after the onset of ILD, it can provide a useful therapeutic strategy in CTD-ILD in humans.…”
Section: Discussionmentioning
confidence: 99%